2012
DOI: 10.1016/j.ophtha.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Retinal Hemangioblastomatosis and Visual Function in Ocular von Hippel-Lindau Disease

Abstract: Objective Characterization of the structural and functional progression of ocular von Hippel-Lindau (VHL) disease and analysis of patient factors influencing disease progression. Design Retrospective analysis of a case series from a longitudinal observational study. Participants Two hundred and forty-nine participants with clinically-defined systemic VHL disease and greater than two years of ophthalmic follow-up. Methods Standardized scoring of ocular phenotype and systemic characteristics was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
0
28
0
4
Order By: Relevance
“…They worked on genotype-phenotype correlations and found that the genotype category of the germline VHL mutation was associated with ocular VHL disease progression using Kaplan-Meier time-to-event analyses on the basis of individual participants, even if not significantly associated with disease progression in univariate or multivariate analyses. 56 For example, complete deletion mutation of the VHL gene was protective and development of retinal hemangioblastomas in these patients was significantly lower relative to patients with a missense or protein-truncating mutation. Moreover, those with complete deletions have better visual acuity and decreased incidence of retinal hemangioblastomas.…”
Section: Factors Influencing Hemangioblastoma Progressionmentioning
confidence: 90%
See 2 more Smart Citations
“…They worked on genotype-phenotype correlations and found that the genotype category of the germline VHL mutation was associated with ocular VHL disease progression using Kaplan-Meier time-to-event analyses on the basis of individual participants, even if not significantly associated with disease progression in univariate or multivariate analyses. 56 For example, complete deletion mutation of the VHL gene was protective and development of retinal hemangioblastomas in these patients was significantly lower relative to patients with a missense or protein-truncating mutation. Moreover, those with complete deletions have better visual acuity and decreased incidence of retinal hemangioblastomas.…”
Section: Factors Influencing Hemangioblastoma Progressionmentioning
confidence: 90%
“…Toy et al 56 reported the following factors to be significantly linked to anatomic progression of retinal hemangioblastomas: younger age at onset of ocular VHL disease, younger age at baseline visit, and involvement of the fellow eye with ocular VHL disease. They did not find a correlation between the presence of extraocular VHL disease and anatomic progression of ocular VHL disease.…”
Section: Factors Influencing Hemangioblastoma Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 49% and 62% of VHL patients will develop retinal hemangioblastomas (Poulsen et al, 2010; Toy et al, 2012; Wittström et al, 2014). Retinal hemangioblastomas are often the first manifestation of VHL, with the lowest median age of onset (21 years) among the various manifestations of VHL (Kreusel et al, 2006; Poulsen et al, 2010).…”
Section: Central Nervous System Lesionsmentioning
confidence: 99%
“…15B), 26 and retinal hemangioblastomas are a feature of von Hippel-Lindau disease. [27][28][29][30] Joubert syndrome is characterized by abnormal eye movements and optic nerve and/or chorioretinal coloboma, less commonly retinal abnormalities. 31 Several ocular abnormalities occur in congenital muscular dystrophies such as WalkerWarburg syndrome, including cataracts, microphthalmos, buphthalmos, retinal pigmentary changes, PHPV, retinal detachment, vitreous hemorrhage, coloboma, Peter anomaly, and ONH.…”
Section: Orbital and Ocular Abnormalities With Central Nervous Systemmentioning
confidence: 99%